2017
DOI: 10.1200/jco.2017.35.15_suppl.1570
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of metaplastic breast cancer: A review of 2,500 cases from the national cancer database.

Abstract: 1570 Background: Metaplastic breast cancer (MBC) is a rare, aggressive, sarcomatoid breast cancer that was first described in 1973 but only became recognized as a histologically distinct entity in 2000. Given the paucity of data on the epidemiology of MBC, we performed a population-based analysis to delineate sociodemographic and clinicopathological characteristics associated with increased likelihood of MBC diagnosis. Methods: Adult female breast cancer patients with stage I-III MBC and non-MBC histology dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Notably, as compared to other breast cancer subtypes, axillary nodal involvement are only found in 8-40% of cases and haematogenous spread to the bone and lungs is more common, as compared to the lymphatic route [4].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Notably, as compared to other breast cancer subtypes, axillary nodal involvement are only found in 8-40% of cases and haematogenous spread to the bone and lungs is more common, as compared to the lymphatic route [4].…”
Section: Discussionmentioning
confidence: 92%
“…It commonly affects women in the age 49-59 group, with most patients presenting with larger size and more advanced tumours, compared to those with invasive ductal carcinoma, which is the most common type of breast cancer [3]. In an epidemiological study by the National Cancer Database by Campbell et al [4] women of African descent and low socioeconomic status were found to be at increased risk for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations